Major Evolutionary Transitions and the Roles of Facilitation and Information in Ecosystem Transformations - Robin, Amanda N.; Denton, Kaleda K.; Horna Lowell, Eva S.; Dulay, Tanner; Ebrahimi, Saba; Johnson, Gina C.; Mai, Davis; O’Fallon, Sean; Philson, Conner S.; Speck, Hayden P.; Zhang, Xinhui Paige; Nonacs, Peter (Frontiers in Ecology and Evolution, 2021)
A small number of evolutionary adaptations attract attention as being extraordinary. Maynard Smith and Szathmáry in their 1995 book identified eight such “Major Evolutionary Transitions” (METs), which fall into two classes: previously independently-reproducing entities combining into higher, integrated levels of association; or changes in information storage and transmittal across individuals. Szathmáry later explicitly defined METs in relation to organismal complexity, irrespective of broader ecosystem-level effects. This divorce between evolutionary and ecological consequences qualifies eukaryotes, for example, as a MET although they failed to significantly alter ecosystems for almost a billion years. Additionally, this definition excludes revolutionary innovations not fitting into either MET type (e.g., photosynthesis). We recombine evolution with ecology to explore how and why entire ecosystems were newly created or irreversibly altered – as Major System Transitions (MSTs). In doing so, we highlight the importance of remarkably successful morphological adaptations that spread through populations because of their immediate, direct-fitness advantages for individuals. These are Major Competitive Transitions, or MCTs. Importantly, we argue that often multiple METs and MCTs must be present to produce MSTs. Therefore, we introduce the concepts of Facilitating Evolutionary Transitions (FETs) and Catalysts as key events or agents in evolutionary history that do not individually cause MSTs, but are essential parts of synergies that do. We further elucidate the role of information in MSTs as transitions across five increasing levels: I. Encoded; II. Epigenomic; III. Learned; IV. Inscribed; and V. Dark Information. The latter is ‘authored’ by complex computer algorithms rather than biological organisms. Level IV has arguably made humans a MST, and V perhaps makes us a FET for a future transition that melds biotic and abiotic life into one entity.